The Electrical Characteristic of Plasma Discharge by Using Different Operating Conditions in Vanadium Sputtering System - Roomy, Harakat Mohsin; Abed Al-Gaffer, Alaa Nazar; Khalaf, Mohammed K (Al-Nahrain Journal of Science, 2019)
This paper report the experimental results of the effects of the inter-electrode distances and applied voltages for various operating pressure on the electrical characteristic of plasma discharge. We have studied the Current-voltage (I-V) characteristics and discharge current – gas pressure (I-P) for different inter-electrode gaps (3, 4, 5, 6, and 8) cm of the planar magnetron discharge. Also Paschen curve were measured at different spacing, The Paschen curves in Ar gas show that the breakdown voltage between two electrodes is a function of pd (The product of the pressure inside the chamber and distance between the electrodes). The results show the sensitivity of electrode separation lead to change the electrical characteristic of generating plasma; where The I-V characteristics of argon gas were deduced as a plasma system operated in abnormal glow discharge region, which is very impotent deposition sputtering. As well as the discharge current was increased for argon plasma discharge with the increasing of the working pressure lead to increase the deposition rate. Paschen curve is analyses at different working pressures and gap distances between two electrodes .the behavior between discharge current and discharge voltage for different gap distances between two electrodes was nonlinear, In addition the experimental finding validated that the suitable electrical characteristics of glow discharge current as a function to applied voltage for varying argon gas pressure at inter-electrode spacing equal to 5 cm.